Genomic Evidence for Complex Domestication History of the Cultivated Tomato in Latin America. (7th January 2020) - Razifard, Hamid; Ramos, Alexis; Della Valle, Audrey L; Bodary, Cooper; Goetz, Erika; Manser, Elizabeth J; Li, Xiang; Zhang, Lei; Visa, Sofia; Tieman, Denise; van der Knaap, Esther; Caicedo, Ana L
Abstract: The process of plant domestication is often protracted, involving underexplored intermediate stages with important implications for the evolutionary trajectories of domestication traits. Previously, tomato domestication history has been thought to involve two major transitions: one from wild Solanum pimpinellifolium L. to a semidomesticated intermediate, S. lycopersicum L. var. cerasiforme (SLC) in South America, and a second transition from SLC to fully domesticated S. lycopersicum L. var. lycopersicum in Mesoamerica. In this study, we employ population genomic methods to reconstruct tomato domestication history, focusing on the evolutionary changes occurring in the intermediate stages. Our results suggest that the origin of SLC may predate domestication, and that many traits considered typical of cultivated tomatoes arose in South American SLC, but were lost or diminished once these partially domesticated forms spread northward. These traits were then likely reselected in a convergent fashion in the common cultivated tomato, prior to its expansion around the world. Based on these findings, we reveal complexities in the intermediate stage of tomato domestication and provide insight on trajectories of genes and phenotypes involved in tomato domestication syndrome. Our results also allow us to identify underexplored germplasm that harbors useful alleles for crop improvement.